Sustainability of the Different Rice Cultivation Practices in Yogyakarta, Indonesia - Ikhsan Adi Pratama; Any Suryantini; Hani Perwitasari (Caraka Tani: Journal of Sustainable Agriculture, 2024)
The current food crisis has become a serious threat to humanity. Other issues such as climate change, farmer regeneration, and excessive use of chemical inputs at the producer level threaten sustainability in agriculture. The sustainability of agricultural practices among farmers remains questionable due to the small number of organic farmers in Indonesia. The purpose of this study was to determine the level of sustainability of rice cultivation and the factors that influence the sustainability of rice cultivation in various types of cultivation in Yogyakarta. Research on farm sustainability that is analyzed in a multidimensional (5 dimensions) and compares 3 types of cultivation has not been widely carried out in Indonesia. This research was conducted in Bantul and Sleman with 90 respondents. The analysis method used Multidimensional Scaling-RAPFISH and Tobit regression. The results showed interesting findings where the 3 types of rice cultivation are in the sufficient (moderately sustainable) category even though the 3 have differences in the use of inputs, especially in the ecological dimension. The factors of education, frequency of attending extension and activity in farmer groups, the use of good agricultural practices, land ownership, and type of cultivation had a positive effect on increasing the sustainability of rice cultivation in various types of cultivation in Yogyakarta. The results of this research have an impact on agricultural extension field education provided by the government to increase the sustainability of rice cultivation in Yogyakarta. It is recommended that the 3 types of rice farmers to pay more attention to the use of Good Agricultural Practices (GAP) to increase sustainability.